Morphometric determination of sex of hyoid bone - V Savitha; R Sunitha; B M Sharada (National Journal of Clinical Anatomy, 2019)
Background and Objectives The hyoid bone shows sexually dimorphic features, which could be used in the sex determination aspect of establishing the biological profile in the remains of skeleton. The aim of this study was to investigate morphometrical variations of the hyoid bone in South Indian population. Materials and Methods A total of 60 adult larynx specimens (30 male and 30 female) with attached hyoid bone were dissected out from postmortem cadavers. The infrahyoid muscles and thyrohyoid membrane were removed. Hyoid bone was dissected and dried completely. Total 10 measurements like length of each greater cornua, length of body, major transverse axis, total hyoid length on both the sides, breadth of hyoid, and height of body of hyoid were taken on each hyoid bone using a digital Vernier caliper. Results The range, mean, standard deviation, and level of significance of all 10 parameters of hyoid bone were calculated using standard statistical method. Most of the parameters showed significant difference between the values of male and female hyoid bones. Conclusion Values obtained for all 10 parameters of hyoid bone were higher in males compared with females, which is suggestive that male hyoid bones are larger in size compared with female hyoid bones.